An N-ethyl-n-nitrosourea induced corticotropin-releasing hormone promoter mutation provides a mouse model for endogenous glucocorticoid excess - Bentley, L; Esapa, C; Nesbit, M; Head, R; Evans, H; Lath, D; Scudamore, C; Hough, T; Podrini, C; Hannan, F; Fraser, W; Croucher, P; et al. (2014)
Cushing's syndrome, which is characterized by excessive circulating glucocorticoid concentrations, maybe due to ACTH-dependent or -independent causes that include anterior pituitary and adrenal cortical tumors, respectively. ACTH secretion is stimulated by CRH, and we report a mouse model for Cushing's syndrome due to an N-ethyl-N-nitrosourea (ENU) induced Crh mutation at -120 bp of the promoter region, which significantly increased luciferase reporter activity and was thus a gain-of-function mutation. Crh -120/+ mice, when compared with wild-type littermates, had obesity, muscle wasting, thin skin, hair loss, and elevated plasma and urinary concentrations of corticosterone. In addition, Crh-120/+ mice had hyperglycemia, hyperfructosaminemia, hyperinsulinemia, hypercholesterolemia, hypertriglyceridemia, and hyperleptinemia but normal adiponectin. Crh -120/+ mice also had low bone mineral density, hypercalcemia, hypercalciuria, and decreased concentrations of plasma PTH and osteocalcin. Bone histomorphometry revealed Crh-120/+ mice to have significant reductions in mineralizing surface area, mineral apposition, bone formation rates, osteoblast number, and the percentage of corticoendosteal bone covered by osteoblasts, which was accompanied by an increase in adipocytes in the bone marrow. Thus, a mouse model for Cushing's syndrome has been established, and this will help in further elucidating the pathophysiological effects of glucocorticoid excess and in evaluating treatments for corticosteroid-induced osteoporosis. Copyright © 2014 by the Endocrine Society Printed in U.S.A.